Rethinking the distinction between job burnout and depression: the mediating role of stress among healthcare professionals in Ecuador - Cisneros-Vidal, María Aranzazu; Peñaherrera-Aguirre, Mateo; Vaca-Gallegos, Silvia L.; Paladines, Belén; Ruisoto, Pablo (Frontiers in Psychology, 2025)
BackgroundThe distinction between job burnout and depression remains debated, particularly among healthcare professionals exposed to chronic work-related stress. This study examined the mediating role of psychological stress in the relationship between job burnout and depression in an Ecuadorian context.MethodsA cross-sectional sample of 437 physicians and nurses was recruited with the support of Ecuadorian Ministry of Public Health. Participants completed the PHQ-9, the Perceived Stress Scale (PSS-10), and the Spanish version of the Maslach Burnout Inventory–Human Services Survey (MBI-HSS). Confirmatory factor analysis was used to assess the validity of all instruments. A structural equation model tested the mediating effect of psychological stress, and multi-group analyses evaluated measurement invariance by gender.ResultsConfirmatory factor analysis supported the latent structures of the PSS-10 and PHQ-9, while only the personal accomplishment subscale of the MBI-HSS demonstrated satisfactory psychometric properties in this sample. The structural equation model showed that psychological stress partially mediated the association between personal accomplishment and depressive symptoms. Measurement invariance across gender was supported, although males and females exhibited different symptom patterns: Men reported more cognitive-affective symptoms, while women endorsed more somatic and concentration-motor features.ConclusionThese findings support the interpretation of job burnout as a potential work-related manifestation of depression, with psychological stress functioning as a transdiagnostic mechanism. From a public health perspective, interventions should target not only individual-level symptoms but also systemic occupational stressors that shape mental health outcomes among healthcare professionals.